The Usage Specification of Registers in Social Media Instagram - Maharani, Sang Ayu Isnu; Mulyawan, I Wayan (Lingual Journal of Language and Culture, 2021)
This research is entitled ‘The Usage Specification of Registers in Social Media Instagram’. The aims of this research are identifying and mapping the usage specification of registers in social media Instagram. It also aims at finding find out the function of the usage of the registers. This research is a combination of qualitative and quantitative research. The method applied for this research was observation method with note-taking techniques. The method used to analyze the data was discourse analysis method. To answer the problems formulated in this research, the register theory of Halliday was applied (1994).   Keywords: specification, register, social media, instagram This research is entitled ‘The Usage Specification of Registers in Social Media Instagram’. The aims of this research are identifying and mapping the usage specification of registers in social media Instagram. It also aims at finding find out the function of the usage of the registers. This research is a combination of qualitative and quantitative research. The method applied for this research was observation method with note-taking techniques. The method used to analyze the data was discourse analysis method. To answer the problems formulated in this research, the register theory of Halliday was applied (1994).   Keywords: specification, register, social media, instagram